Descriptive report on the CAMEL-based performance of a foreign bank in Bangladesh: a Case of Commercial Bank of Ceylon, PLC - Crowley, Stella Scholastica (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.